Differential frequency in imaging‐based outcome measurement: Bias in real‐world oncology comparative‐effectiveness studies. Issue 1 (21st July 2021) - Adamson, Blythe J. S.; Ma, Xinran; Griffith, Sandra D.; Sweeney, Elizabeth M.; Sarkar, Somnath; Bourla, Ariel B.
Abstract: Background: Comparative‐effectiveness studies using real‐world data (RWD) can be susceptible to surveillance bias. In solid tumor oncology studies, analyses of endpoints such as progression‐free survival (PFS) are based on progression events detected by imaging assessments. This study aimed to evaluate the potential bias introduced by differential imaging assessment frequency when using electronic health record (EHR)‐derived data to investigate the comparative effectiveness of cancer therapies. Methods: Using a nationwide de‐identified EHR‐derived database, we first analyzed imaging assessment frequency patterns in patients diagnosed with advanced non‐small cell lung cancer (aNSCLC). We used those RWD inputs to develop a discrete event simulation model of two treatments where disease progression was the outcome and PFS was the endpoint. Using this model, we induced bias with differential imaging assessment timing and quantified its effect on observed versus true treatment effectiveness. We assessed percent bias in the estimated hazard ratio (HR). Results: The frequency of assessments differed by cancer treatment types. In simulated comparative‐effectiveness studies, PFS HRs estimated using real‐world imaging assessment frequencies differed from the true HR by less than 10% in all scenarios (range: 0.4% to −9.6%). The greatest risk of biased effect estimates was found comparing treatments with widely different imaging frequencies, most exaggerated in disease settings where time to progression is very short. Conclusions: This study provided evidence that the frequency of imaging assessments to detect disease progression can differ by treatment type in real‐world patients with cancer and may induce some bias in comparative‐effectiveness studies in some situations.